Influence of fish aggregating devices on the livelihood assets of artisanal fishers in the Caribbean. (1st September 2019) - Montes, Nancy; Sidman, Charles; Lorenzen, Kai; Tamura, Minoru; Ishida, Mitsuhiro
Abstract: Harvesting of pelagic fishery resources is facilitated by using fish aggregation devices (FADs). Moored FADs are manmade structures that attract pelagic fish, thereby aggregating this thinly distributed resource in a known location where it can be effectively targeted. Use of moored FADs has been actively promoted in artisanal fisheries, including those of many island nations, in order to increase food security, improve livelihoods and safety-at-sea for fishers. Using structured face-to-face interviews of 316 artisanal coastal fishers across five Eastern Caribbean island nations, we studied perceived and self-reported livelihood assets (natural, financial, physical, social and human) of non-users, long-term users and recent adopters of moored FAD fishing. Moored FAD fishers were more strongly dependent on fishing as an income source than non-users. Moored FAD fishing is attracting new younger and more educated adults to the fishing occupation, as opposed to converting fishers engaged in other types of fishing activities. Over the past five years, all groups on average perceived a decline in natural and financial assets, but an increase in physical and social assets. Trends perceived by long-term users and non-users were similar in magnitude, whereas recent adopters of moored FAD fishing perceived weaker declines and stronger increases in livelihood assets than the other two groups. We conclude that users of moored FADs perceive greater livelihood benefits compared to non-users. Highlights: Over time, fishers perceived significant changes in the different livelihood assets. Physical and social assets showed a perceived increase over the five-year timeframe, while natural and financial assets were considered to have decreased overtime. Moored FAD user tended to perceived significantly greater scores for the natural and financial assets than non-FAD users. Moored FAD fishing is attracting new younger and more educated adults to the fishing occupation.